Pre-treatment of Lobster Shell Using Hydrochloric Acid for Nanochitosan Production - Safrina, Dyah; Ulfa Safitri, Anisa; Suptijah, Pipih; Fariz Pari, Rizfi (Journal of Marine and Coastal Science, 2023)
Lobster shells are a by-product that can be used as a raw material for making chitin and chitosan. However, lobster shells contain a high amount of minerals that cover the chitin polymer on the shell. This chitin can be converted into chitosan by deacetylation process. Efforts that can be made to increase the efficiency of the chitosan extraction process from lobster shells are by pre-treatment using hydrochloric acid. The purpose of this study was to determine the pre-treatment time of lobster shells with hydrochloric acid and to produce nanochitosan from lobster shells. The results of this study indicate that the pretreatment time has a significant effect on the yield value of chitosan. The highest yield of chitosan was produced from the acid pre-treatment with a soaking time of 120 hours with a value of 15,6%. The quality of lobster chitosan from the best treatment has met the quality requirements based on SNI. Nanochitosan was successfully synthesized by ionic gelation method with a particle size of 357,76 nm and spherical shape based on SEM photos. Lobster nanochitosan has the potential to be applied in various fields, such as food, agriculture,and biomedical.